2018
DOI: 10.1371/journal.pone.0202406
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of soluble ST2 in adolescent and adult patients with complex congenital heart disease

Abstract: BackgroundSoluble suppression of tumorogenicity 2 (sST2) has been shown to be of prognostic value in patients with chronic and acute left heart failure. The present study aims to assess the predictive value of sST2 levels in adult patients with complex congenital heart disease (CHD).MethodsIn 169 consecutive patients with complex CHD and a mean age of 28.2 ± 12.0 years, sST2 levels were compared to 32 healthy controls and associated with clinical status as well as the occurrence of major adverse cardiac events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 34 publications
0
18
1
Order By: Relevance
“…In our study, sST2 and NT-proBNP levels were not correlated in complex ACHD. In the first and only study previously investigating sST2 in patients with complex ACHD, only a very weak correlation was found between sST2 and NT-proBNP (r=0.29, p<0.001) 7. This may suggest that sST2 is involved in another pathophysiological pathway than NT-proBNP regarding myocardial adaptation and dysfunction.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…In our study, sST2 and NT-proBNP levels were not correlated in complex ACHD. In the first and only study previously investigating sST2 in patients with complex ACHD, only a very weak correlation was found between sST2 and NT-proBNP (r=0.29, p<0.001) 7. This may suggest that sST2 is involved in another pathophysiological pathway than NT-proBNP regarding myocardial adaptation and dysfunction.…”
Section: Discussionmentioning
confidence: 82%
“…As sST2 has been investigated extensively in HF, it has only been described once in ACHD. Laqqan et al 7 investigated sST2 in complex ACHD patients with a wide age range (12–70 years) and identified sST2 as strong prognostic biomarker. The prognostic value of sST2 in patients with chronic and acute HF has been established firmly and is described by Aimo et al in two meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At enrollment, a structured protocol including a 12-lead surface electrocardiogram, a physical examination, measurement of blood pressure and transcutaneous oxygen saturation at rest, two-dimensional echocardiography as well as a venous blood draw for routine laboratory parameters and blood sampling were performed. The study protocol has been described in detail previously [24]. Follow-up visits were performed annually according to the above mentioned protocol and with special emphasis on the occurrence or presence of overt heart failure (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…It was also stated that ST2 added additional value to NT-proBNP in predicting mortality although it did not exceed NT-proBNP in predicting hospital admission. In addition, it was showed that NT-proBNP was preferable to ST2 in predicting acute heart failure 35,36 events.…”
Section: Resultsmentioning
confidence: 99%